Impact of Pore Size and Defects on the Selective Adsorption of Acetylene in Alkyne‐Functionalized Nickel(II)‐Pyrazolate‐Based MOFs. Issue 46 (9th July 2021) - Afshariazar, Farzaneh; Morsali, Ali; Sorbara, Simona; Padial, Natalia M.; Roldan‐Molina, Esther; Oltra, J. Enrique; Colombo, Valentina; Navarro, Jorge A. R.
Abstract: C2 H2 /CO2 separation is a highly challenging process as a consequence of their similar physicochemical properties. In this work we have explored, by static and dynamic gas sorption techniques and computational modelling, the suitability of a series of two isoreticular robust Ni(II)pyrazolate‐based MOFs, bearing alkyne moieties on the ligand backbones, for C2 H2 /CO2 separation. The results are consistent with high adsorption capacity and selectivity of the essayed systems towards C2 H2 molecules. Furthermore, a post‐synthetic treatment with KOH ethanolic solution gives rise to linker vacancy defects and incorporation of extraframework potassium ions. Creation of defects is responsible for increased adsorption capacity for both gases, however, strong interactions of the cluster basic sites and extraframework potassium cations with CO2 molecules are responsible for a lowering of C2 H2 over CO2 selectivity. Abstract : Robust defective nickel(II) pyrazolate‐based MOFs, bearing alkyne moieties on the organic spacers have been explored for C2 H2 /CO2 separation. As proven by static and dynamic gas adsorption and computational modelling the non‐defective34 systems give rise to selective interactions with C2 H2 over CO2 as a result of a mixture of pore confinement and H‐bonding and alkyne‐alkyne interactions. Creation of defects is responsible for strong interactions of cluster basic sites and extraframework potassium cations with CO2 with a concomitant lowering of C2 H2 over CO2 selectivity.